2020
DOI: 10.1055/s-0040-1708539
|View full text |Cite
|
Sign up to set email alerts
|

Optic Atrophy and Generalized Chorea in a Patient Harboring an OPA10/RTN4IP1 Pathogenic Variant

Abstract: RTN4IP1 pathogenic variants (OPA10 syndrome) have been described in patients with early-onset recessive optic neuropathy and recently associated with a broader clinical spectrum, from isolated optic neuropathy to severe encephalopathies with epilepsy. Here we present a case of a patient with a complex clinical picture characterized by bilateral optic nerve atrophy, horizontal nystagmus, myopia, mild intellectual disability, generalized chorea, isolated small subependymal heterotopia, and asynchronous self-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Our results may also provide insights into the treatment of patients with genetic defects of RTN4IP1. These patients suffer from optic neuropathy and ataxia 37,38,[61][62][63] , and our results suggest that delivery of antioxidant molecules or CoQ supplements may help to relieve these symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…Our results may also provide insights into the treatment of patients with genetic defects of RTN4IP1. These patients suffer from optic neuropathy and ataxia 37,38,[61][62][63] , and our results suggest that delivery of antioxidant molecules or CoQ supplements may help to relieve these symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…To date, several mutations have been identified in different patients, including 15 single-nucleotide change mutations and two deletion mutations) in three separate studies [3,4,[10][11][12][13][14]34,35], as summarized in Table S1 and shown in Figure 5C. Thereof, 15 variants cause various single amino acid changes, two variants lead to truncations, and one variant presumably causes aberrant splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Optic atrophy, seizures, nystagmus, and global developmental delay are the most common symptoms associated with pathogenic variants in the RTN4IP1. In addition, deafness, brain MRI abnormalities, stridor, and abnormal electroencephalograms were seen in severely affected patients with premature death due to the deleterious effect of the variants on RTN4IP1 activity and structure [9,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, only 1 of 15 (6.7%) individuals with isolated OA had a LOF variant. Although the p.(Arg103His) variant is believed to cause a milder isolated ocular phenotype, neurological impairment with generalized chorea, intellectual disability, and midbrain MRI abnormalities have been observed in 1 homozygote (5). To date, only 1 case has been reported with a large deletion spanning the entire gene in RTN4IP1 -associated disease.…”
mentioning
confidence: 99%